Kyrgyz Republic : Poverty Reduction Strategy Paper; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2007)
This Joint Staff Advisory Note (JSAN) highlights the Poverty Reduction Strategy Paper-Country Development Strategy (PRSP-CDS) for the Kyrgyz Republic for 2007-10. The Kyrgyz authorities' CDS for 2007-10 builds on the policy experience from the National Poverty Reduction Strategy (NPRS). This JSAN provides advice on key priorities for strengthening the strategy and promoting the effective implementation of CDS. It reviews poverty trends, macroeconomic and sectoral policies in support of the strategy, and the mechanisms for monitoring and evaluating progress.